Ocular non-Hodgkin lymphoma: a report of two cases and review of the literature (Mediscope, 2018)
In this article, two cases of non-Hodgkin lymphomas (NHL) occurring at an unusual site were reported. The first case was a male patient aged 60 years hailing from Debidwar, Comilla came with the complaint of gradually increasing mass in the left eyelid for two years. Fine-needle aspiration (FNA) and histopathology of his lesion revealed NHL, which on immunohistochemistry showed to be of B-cell origin. A debulking operation was done in National Institute of Ophthalmology & Hospital, Dhaka and he was sent for chemotherapy. The second case was also a male aged 35 years from Muladi, Barisal who presented with gradually increasing bilateral masses on both the upper eyelids for six months. The results of FNA of the eyelid tumors were suggestive of NHL that was subsequently confirmed by histopathology. Immunohistochemistry showed the tumor to be of B-cell origin.Mediscope Vol. 5, No. 2: Jul 2018, Page 36-41